INDICATORS OF ABDOMINAL OBESITY: WAIST CIRCUMFERENCE AND WAIST-TO-HIP RATIO IN ADOLESCENTS OF NORTH MACEDONIA - Bojadzieva, Biljana Stojanoska; Matveeva, Niki; Zafirova, Biljana; Trpkovska, Biljana; Chadikovska, Elizabeta; Angelovska, Irina (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
Obesity in children and adolescents in the world is reaching a scale of an epidemic. It is considered the most widespread disease in children in many countries, especially in developed countries. The aim of this study was to define WC and WHR among Macedonian adolescents aged 11 to 14 years. A cross-sectional study was performed in 2013-2015, comprising a sample of 1267 adolescents of the Republic of Macedonia aged 11 to 14 years; 646 males and 621 females. Weight, height, body mass index (BMI), waist circumference (WC), hip circumference (HC) and waist-to-hip ratio (WHR) were measured and percentiles were calculated using Coleâ€™s Lambda, Mu and Sigma (LMS) method. The relation between WHR and general obesity, as defined by the International Obesity Task Force, was investigated with receiver operating characteristic (ROC) analysis. The boys had statistically significant higher values â€‹â€‹in all anthropometric measures, except in HC where statistically significant gender differences were not found. BMI, WC, and HC increased with the age. The obtained reference percentile curves can be used temporarily for obesity screening in children and adolescents. Keywords : abdominal obesity; adolescents, anthropometric measurements. https://doi.org/10.55302/JMS2141138sb